Integrated Set of Information Systems (ISIS) application for computerized storage and retrieval of the presidential issuances, 1972-1977, at the Technology Resource Center - Co, Alice N. (1979)
This work is a study of the initial application in the Philippines of the Integrated Set of Information Systems (ISIS), a collection of computer software for the processing of bibliographic data developed by the Central Library and Documentation Branch of the International Labor Office, Geneva. The aims of this study are : 1. To study the application of ISIS in the computerized storage and retrieval of information contained in the Presidential Issuances, 1972-1977, as implemented by the Vital Documents (VIDOC) Project of the Technology Resource Center. 2. To discuss the problems encountered at TRC in the use of ISIS and the local solutions to such problems; and 3. To evaluate the effectivity of this application of ISIS.